Integrationen mellan hög- och lågstatus samarbeten: En kvalitativ innehållsanalys av Balenciaga x Crocs och Gosha Rubchinskiy x Burberry — kollaborationerna som sägs vara ojämna enligt Vogue - Churilova,Ekaterina; Christensson,Amelie (2018)
This writing assignment is a study about the two fashion collaborations: Balenciaga x Crocs and Gosha Rubchinskiy x Burberry, which were launched during Paris Fashion Week and Goshas SS18-show in Russia, in 2017. These collaborations have been assessed to be created unequally by Vogue Magazine, but the question is if they really are. Vogue believes that the partnerships are not created evenly, since the parties in the collaborations have distinct brand identities. The writing assignment aims to examine and get an understanding of potential motives behind the co-operations between Balenciaga x Crocs and Gosha Rubchinskiy x Burberry. Also to investigate whether the two collaborations are uneven as Vogue claims, according to the theory of the status market by the social economist Patrik Asper. The analysis was carried out through a qualitative content analysis and treats 16 selected fashion articles, of which half of them talks about Balenciaga x Crocs and the remaining eight are discussing Gosha Rubchinskiy x Burberry. The results of the analysis show that potential causes behind the collaborations are about financial interests from the well-established fashion houses Balenciaga and Gosha Rubchinskiy. Also that street-style influencers and fashion trends can be the basis for the creation of the collaborations. In conclusion, the analysis shows that the two collaborations are not estimated to be uneven according to Asper's theory of the status market. His theory is rather saying that the co-operations between Balenciaga x Crocs and Gosha Rubchinskiy x Burberry are created equal, since low status brands, like Crocs and Gosha Rubchinskiy, have gained more status through current fashion trends.
Keywords: Fashion collaboration; Vogue Magazine; Balenciaga; Crocs; Gosha Rubchinskiy; Burberry; Status market; Social media